2020
DOI: 10.1021/acs.chemmater.0c04570
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-Ion Shuttle Battery with High Volumetric Energy Density

Abstract: With the increasing development of electric vehicles and portable devices, there is a strong requirement for high-energy batteries. To improve battery energy, multielectron transfer electrode reactions can be applied. Previously, batteries based on fluoride-ion shuttle (F– ion shuttle batteries, FiBs) have been reported, utilizing electrodes with multielectron transfer reactions. Although these FiBs exhibit high theoretical energy densities, reported capacities are significantly less than theoretical values. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…The impedances of Cu and Cu−Pb were evaluated by EIS, as shown in Figure 5. In the equivalent circuit, R, CPE, and W s represented resistances, constant phase elements, and finite-diffusion Warburg resistance, respectively, where the high-frequency and medium-frequency semicircles could be assigned to grain-boundary (which can be observed in Cu-bulk TEM images in our previous work 38 ) and chargetransfer effects in the working electrode. 39 Although the suppressed impedance in Cu−Pb verified the promotion effect of the nanocomposite strategy, such suppressions on impedances were not so significant as the optimizations on electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The impedances of Cu and Cu−Pb were evaluated by EIS, as shown in Figure 5. In the equivalent circuit, R, CPE, and W s represented resistances, constant phase elements, and finite-diffusion Warburg resistance, respectively, where the high-frequency and medium-frequency semicircles could be assigned to grain-boundary (which can be observed in Cu-bulk TEM images in our previous work 38 ) and chargetransfer effects in the working electrode. 39 Although the suppressed impedance in Cu−Pb verified the promotion effect of the nanocomposite strategy, such suppressions on impedances were not so significant as the optimizations on electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, 14,27,28 we demonstrated that the 3dtransition-metal cathode (Cu, Co, and Ni) and the selfgenerated La/LaF 3 anode in thin-film all-solid-state FIBs show clear charge−discharge behavior. The combinations of Cu, Co, and Ni cathodes and representative anodes (La/LaF 3 , Ce/ CeF 2 , Pb/PbF 2 , etc.)…”
Section: Introductionmentioning
confidence: 89%
“…S2, ESI†). It is reasonable that the formed LaF 3 is stable under our measurement conditions because the reduction potential of LaF 3 to La is −2.4 V vs. Pb/PbF 2 , 12 which is a much lower potential than that in our charge and discharge measurements. On the basis of ADF STEM images in Fig.…”
Section: Resultsmentioning
confidence: 63%
“…11 To solve this fluorination issue on cathode metals, several morphological control strategies of metals have been proposed such as forming nanoparticles and thin films. 1,9,11,12 However, the proposed methodologies significantly restrict the design of electrodes, and moreover they would cause other technical difficulties, i.e. , oxidation of electrodes or poor electric contact between electrodes and electrolytes.…”
Section: Introductionmentioning
confidence: 99%